ROSEN'S Emergency Medicine Concepts and Clinical Practice - Wall, Ron M.; Hockberger, Robert S.; Gausche-Hill, Marianne (Elsevier, 2023)
For nearly 40 years, Rosen's Emergency Medicine has provided emergency physicians, residents, physician assistants, and other emergency medicine practitioners with authoritative, accessible, and comprehensive information in this rapidly evolving field. The fully revised 10th Edition delivers practical, evidence-based knowledge and specific recommendations from clinical experts in a clear, precise format, with focused writing, current references, and extensive use of illustrations to provide definitive guidance for emergency conditions. With coverage ranging from airway management and critical care through diagnosis and treatment of virtually every emergency condition, from highly complex to simple and common, this award-winning, two-volume reference remains your #1 choice for reliable, up-to-date information across the entire spectrum of emergency medicine practice.